Investigation of Attitudes Toward COVID-19 Phobia and COVID-19 Vaccine in Healthcare Professionals in Türkiye - Sultan Yurtsever Çelik; Emine Kır Biçer; Selda Çelik; Nurdan Yıldırım; Yeliz Demirhan; Giray Erdoğan; Gülhan Coşansu; Nermin Olgun (Cerrahpaşa Medical Journal, 2026)
Objective: This study aimed to examine COVID-19 phobia and attitudes toward the COVID-19 vaccine among healthcare professionals. Methods: This descriptive cross-sectional study was conducted between January and March 2021. Ethical approval and Ministry of Health permissions were obtained before the study commenced. A total of 4029 healthcare professionals from 80 different cities across Türkiye participated. Data were collected using the Participant Information Form, the COVID-19 Phobia Scale, and the Attitudes Toward the COVID-19 Vaccine Scale. Results: Of the participants, 82.2% were female, 68.4% were married, and 57% were nurses. COVID-19 phobia was higher among participants with chronic diseases, those working in pandemic hospitals, those caring for COVID-19 patients, those who experienced loss of an acquaintance/relative due to COVID-19, married participants, and those with children. Vaccine attitudes were more positive among married participants, those with children, those with chronic diseases, and those with higher income, whereas more negative attitudes were observed among females and those working in pandemic hospitals. Conclusion: The findings indicate that COVID-19-related experiences may be associated with both phobia levels and vaccination attitudes among healthcare professionals. Psychological preparedness and supportive interventions may help healthcare professionals better cope with future pandemics. Cite this article as: Çelik SY, Biçer EK, Çelik S, et al. Investigation of attitudes toward COVID-19 phobia and COVID-19 vaccine in healthcare professionals in Türkiye. Cerrahpaşa Med J. 2026, 50, 0113, doi: 10.5152/cjm.2026.25113.